SCHOOL BULLYING: REVIEW OF SCIENTIFIC PRODUCTION ON PEDAGOGICAL AND INSTITUTIONAL PROPOSALS FOR COPING (2015–2023) - Gonçalves, Vanessa Costa (Horizontes - Revista de Educação, 2025)
This work aims to explore academic productions in the field of education concerning proposals to address school bullying using the State of Knowledge methodology, by assessing the scientific production from 2015 to 2023. To guide the research, the following questions were observed: what has been academically produced on combating bullying? What is the scope of institutional action in the productions conducted? In attempting to answer these questions, it becomes evident that evaluating academic productions is necessary to understand the identified issues and experiences related to this problem. Additionally, strategies to combat bullying are essential to highlight the approaches adopted by educational institutions as a proposal to address bullying. As a result, it is indicated that a well-structured and inclusive school curriculum can play a significant role in combating bullying within educational institutions.